Human Motion Capture Berbasis Bebas-Model Menggunakan Penanda Fitur Multi Warna Terparameter - Samuel Gandang Gunanto (Institut Seni Indonesia Yogyakarta, 2015)
The utilization of computer vision technology is being developed at this time is the development of science in the realm of digital creative arts, such as animations and games. In this field, computer vision technology plays a role in human motion capture system for generating motion animation of 3D models by real human models through the capture of the camera. With this system of motion generated animation more natural, but the availability of tools and utilization of this technology in the world of animation Indonesia is still very low due to the high price of tools and software used.The reliability of the system is determined by the accuracy of the estimation of the pose of a model, so that the determination of each segment of the human body in the early stages is the key to success. This research manipulate with features multicolored markers on human motion capture system. Markers are positioned on the joints of human motion in a circle, each color is unique. In addition to cheap and easy to implement, aspects of convenience and flexibility in motion are also taken into consideration the application of these markers.Calibration Bouguet to 3 cameras used ranged from 0.11 to 0.16 pixels. While the color detection method Giannakopoulos in this case has a value of error of 0.074582. Both values are supporting reconstruction and pose estimation of human stick figures in 3D is quite good, although quantitatively has a point value of the position estimation error of 4.54 cm 3D features. Keywords: multicolor feature, human motion capture, marker based, free models, animation, game. Abstrak Pemanfaatan teknologi visi komputer yang sedang berkembang saat ini adalah pengembangan di ranah ilmu seni kreatif digital, seperti animasi dan game. Di bidang ini, teknologi visi komputer berperan pada sistem penangkapan gerak manusia untuk membangkitkan animasi gerak model 3D oleh model manusia sesungguhnya melalui penangkapan kamera. Dengan sistem ini gerak animasi yang dihasilkan lebih natural, namun ketersediaan alat dan pemanfaatan teknologi ini di dunia animasi Indonesia masih sangat minim dikarenakan mahalnya harga alat dan perangkat lunak yang dipakai.Kehandalan sistem ini ditentukan oleh ketepatan estimasi dari pose model, sehingga penentuan tiap segmen tubuh manusia di tahapan awal merupakan kunci keberhasilannya. Penelitian ini merekayasa penanda dengan fitur multiwarna pada sistem penangkapan gerak manusia. Penanda diposisikan pada sendi gerak manusia secara melingkar yang masing-masing warna bersifat unik. Selain murah dan mudah diterapkan, aspek kenyamanan dan keluwesan dalam gerak juga menjadi pertimbangan penerapan penanda ini.Kalibrasi Bouguet untuk 3 kamera yang dipakai berkisar antara 0,11-0,16 piksel. Sedangkan deteksi warna metode Giannakopoulos pada kasus ini mempunyai nilai kesalahan sebesar 0,074582. Kedua nilai tersebut mendukung rekonstruksi dan estimasi pose figur tongkat manusia secara 3D yang cukup baik, meskipun secara kuantitatif memiliki nilai kesalahan estimasi titik posisi fitur 3D sebesar 4,54 cm. Kata Kunci : fitur multiwarna, human motion capture, basis penanda, bebas-model, animasi, game.